Experience of applying the metagenomic sequencing method on fragments of the 16S rRNA gene for the detection and identification of natural focal infection pathogens - Oksana V. Vasilieva; Diana V. Ul’shina; Anna S. Volynkina; Sergey V. Pisarenko; Yulia V. Siritsa; Olga A. Gnusareva; Natalia A. Yatsenkо; Alexandr N. Kulichenko (Журнал микробиологии, эпидемиологии и иммунобиологии)
Introduction. Metagenomic sequencing is one of the most promising methods for both the detection and identification of natural focal infection (NFI) pathogens and for determining the species composition of various bacterial communities.